Some observations on the description of the strong verb conjugation in educational materials for the three continental Scandinavian languages: part II – Norwegian and Danish - Naydenov, Vladimir (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2022)
This is the second part of a two-part article which discusses and contrasts the ways in which strong verbs are usually described in educational materials for the three Mainland Scandinavian languages as L2. The second part examines materials for Norwegian and Danish. It is concluded that they tend to place less emphasis on the distinction between ‘strong’ and ‘irregular’ verbs and the regular patterns found in their conjugation than their Swedish counterparts do. Some explanations for this fact are offered.
Keywords: strong verbs; Norwegian; Danish; regularity; didactics